Robotic Teaching Aid for Disabled Children: A Sustainable Solution for Industrial Revolution 4.0 - Zamin, N; I. Arshad, N; Rafiey, N; S. Hashim, A (International Journal of Engineering and Technology, 2018)
Many special needs children suffer from a common characteristics impairment which appear as disability to interpret social cues, fail to use joint-attention tasks as well as a failure in social gaze when communicating.  This what makes them different than the normal children. The results of this difficulty are the special needs children often get frustrated when they are unable to expressively share their feeling and socially interact with the community. This research is investigating the problems faced by autistic, down syndrome and slow learner children to respond and communicate appropriately with the people around them and to propose an efficient approach to improve their social interaction.  Malaysian education policy is to integrate students with learning difficulties or special educational needs.  Thus, the development of a robotic approach using LEGO Mindstorms EV3 to aid the teaching and learning of special needs children especially autism in in Malaysia in introduced in this paper.  Robotic approach in special education provides changes, inclusive and sustainable development of the disabled community towards supporting Industrial Revolution 4.0.